Host genetic factors associated with the range limit of a European hantavirus. Issue 1 (21st October 2021) - Saxenhofer, Moritz; Labutin, Anton; White, Thomas A.; Heckel, Gerald
Abstract: The natural host ranges of many viruses are restricted to very specific taxa. Little is known about the molecular barriers between species that lead to the establishment of this restriction or generally prevent virus emergence in new hosts. Here, we identify genomic polymorphisms in a natural rodent host associated with a strong genetic barrier to the transmission of European Tula orthohantavirus (TULV). We analysed the very abrupt spatial transition between two major phylogenetic clades in TULV across the comparatively much wider natural hybrid zone between evolutionary lineages of their reservoir host, the common vole ( Microtus arvalis ). Genomic scans of 79, 225 single nucleotide polymorphisms (SNPs) in 323 TULV‐infected host individuals detected 30 SNPs that were consistently associated with the TULV clades CEN.S or EST.S in two replicate sampling transects. Focusing the analysis on 199 voles with evidence of genomic admixture at the individual level (0.1–0.9) supported statistical significance for all 30 loci. Host genomic variation at these SNPs explained up to 37.6% of clade‐specific TULV infections. Genes in the vicinity of associated SNPs include SAHH, ITCH and two members of the Syngr gene family, which are involved in functions related to immune response or membrane transport. This study demonstrates the relevance of natural hybrid zones as systems not only for studying processes of evolutionary divergence and speciation, but also for the detection of evolving genetic barriers for specialized parasites.